PERSEPSI PESERTA DIDIK TERHADAP GAYA PEMBELAJARAN GURU PADA PELAJARAN KONSTRUKSI BANGUNAN DI SMK TEKNIK - Farhan Dwi Laksono (CV. ADIBA AISHA AMIRA, 2024)
Learning style is the way how each individual processes information and manages information. In the learning process, each learner usually has a diverse learning style. There are students who understand better if learning through theory, there are also students who more easily understand learning by practice. A good learning style will make it easier for students to follow the learning process. The writing of this article aims to explore learners' perceptions of teachers' learning styles in Building Construction lessons. Descriptive research method was used by interviewing learners who have attended the lesson. The results show that most learners have a positive perspective on the teacher's learning style in Building Construction lessons. There are several factors that help this positive perspective including the teacher's ability to explain learning concepts, and learning media that can be understood. However, there were also some learners who said they needed improvement in their learning approach and understanding. The author aims to provide teachers with insights in improving the quality of their learning, by adapting their learning style to students' preferences